Differences in psychosocial distress among rural and metropolitan health care workers during the COVID‐19 pandemic. (5th May 2022) - Tham, Rachel; Pascoe, Amy; Willis, Karen; Kay, Margaret; Smallwood, Natasha
Abstract: Objective: The Australian COVID‐19 Frontline Healthcare Workers study examined the prevalence and severity of mental health symptoms during the second wave of the COVID‐19 pandemic. This substudy examined the differences in psychological well‐being between rural and metropolitan health care workers (HCWs). Design: A nationwide survey conducted between August and October 2020. Setting and Participants: Australian HCWs were recruited through multiple strategies. Main outcome measures: Demographics, mental health outcomes (anxiety, depression, post‐traumatic stress disorder [PTSD] and burnout). Results: Complete responses were included from 7846 participants, with 1473 (18.8%) in regional or remote ('rural') areas and 81.2% in metropolitan areas. Rural participants were older, more likely to work in allied health, nursing or in health administration, and had worked longer in their profession than metropolitan participants. Levels of resilience were similar ( p  = 0.132), but there was significantly higher prevalence of pre‐COVID‐19 pandemic mental illness in the rural workforce ( p  < 0.001). There were high levels of current mental health issues: moderate–severe PTSD (rural 38.0%; metropolitan 41.0% p  = 0.031); high depersonalisation (rural 18.1%; metropolitan 20.7% p  = 0.047); and high emotional exhaustion (rural 46.5%; metropolitan 43.3% p  = 0.002). Among rural participants, mental health symptoms were associated with younger age, worry about being blamed if they contracted COVID‐19, fear of transmitting COVID‐19 to their family, experiencing worsening relationships and working in primary care or allied health. Conclusion: Despite having low COVID‐19 case numbers in rural Australian health services compared with metropolitan counterparts over the course of 2020, there were widespread mental health impacts on the workforce. Rural health services need specific and flexible training, education, work policies and practices that support psychological well‐being now in preparedness for ongoing or future crises.